Formulation and evaluation of olanzapine loaded chitosan nanoparticles for nose to brain targeting an in vitro and ex vivo toxicity study - J. Joysa Ruby, V. P. Pandey (Journal of Applied Pharmaceutical Science, 2016)
Olanzapine is an atypical antipsychotic drug shows low bioavailability due to extensive first pass metabolism and results in numerous side effects due to non targeted delivery. The present study was aimed to prepare and characterize olanzapine loaded chitosan nanoparticles for nose to brain targeting. The olanzapine loaded chitosan nanoparticles were prepared by ionic gelation of chitosan with tripolyphosphate anions. The formulated nanoparticles showed mean particle size, polydispersity index and zeta potential to be 183.1±8.42 nm, 0.122±0.08, +52.1±2.4 mV respectively. The entrapment efficiency and drug loading was found to be 72.42 ±3.65% and 26 .04± 2.12. In vitro drug release was showed a biphasic release pattern with initial burst release followed by sustained release of formulated nanoparticles. In vitro toxicity studies were carried out on RPMI 2650 human nasal epithelial cell line by MTT assay. The obtained result shows lower toxicity (high IC50 value) of nanoformulation as compared to free drug. Ex vivo histopathological studies were carried out by using excised goat nasal mucosa and the microscopic structure of nasal mucosa shows no significant harmful effects of formulated nanoparticles. These results illustrate that olanzapine loaded chitosan nanoparticles is a potential new delivery system for treatment of depressant when transported via olfactory nasal pathway to the brain.
Keywords: Olanzapine, Ionic cross linking method, nose to brain delivery, chitosan, nanoparticles.